The Effect of Professional Volleyball Players' Mental Endurance, Imagination, and Internal Speech Levels on the Way They Cope with Stress - Özlem Ekizoğlu; Mehmet Acet; Can Toros (IUC University Press, 2024)
The aim of this research is to reveal whether professional volleyball players' mental endurance in sports, visualization in sports, talking to themselves, and strategies for coping with stress in sports differ according to their gender, age, and marital status. In addition, the aim was also to examine the effects of mental endurance in sports, imagery in sports. and self-talk on the strategy of coping with stress in sports. A total of 56 professional volleyball athletes, 33 women and 23 men living in Kütahya, participated in the study. Data were collected with a personal information form and a total of four scales: mental endurance in sports, visualization in sports, self-talk, and strategies for coping with stress in sports inventory. Findings were obtained by independent sample t-test, one-way ANOVA, correlation, and multiple regression analysis using the Statistical Package for Social Sciences version 21.0 software (IBM Corp.; Armonk, NY, USA). As a result, the gender, age, and marital status of the participants did not make a significant difference on their mental endurance and imagination; It was found that those who were single had higher self-talk and stress coping strategy scores than those who were married. In addition, as the participants' ages increase, their stress coping strategy scores decrease and their stress coping strategies in sports. It has been found that it affects mental endurance in sports by 15%, imagination in sports by 38%, and self-talk by 43%.